Scleractinian corals from the upper Berriasian of central Europe and comparison with contemporaneous coral assemblages - Baron-Szabo, Rosemarie Christine (Zootaxa, 2018)
Scleractinian coral faunas from the upper Berriasian part of the Oehrli Formation of western Austria (Vorarlberg) and eastern Switzerland (Canton of Appenzell) are taxonomically described for the first time. Furthermore, scleractinian corals of the upper Berriasian part of the Oehrli Formation of the Swiss Cantons of Nidwalden and Uri are revised based on the study of type material. Lectotypes are designated for the species Dimorphocoeniopsis alpina (Koby, 1896) and Pleurophyllia tobleri (Koby, 1896). Sixty-one species belonging to 43 genera and 18 families were identified, making the coral fauna of the upper Oehrli Formation by far the most diverse among the Berriasian assemblages: Actinastrea pseudominima (Koby), A. sp., Adelocoenia bulgarica (Toula)(new combination), A. hexaphyllia (d’Orbigny)(new combination), A. radisensis (d’Orbigny)(new combination), Allocoeniopsis luciensis (d’Orbigny), Amphiaulastrea sp., Astraeofungia cf. decipiens (Michelin), Cladophyllia conybearei Milne Edwards & Haime, Columnocoenia ksiazkiewiczi Morycowa, Comoseris jireceki Toula, Complexastrea seriata Turnšek, C. lobata Geyer, Cycloria mariscali (Felix)(new combination), Dermosmilia capitata (Koby), D. simplex Koby, Dimorphastrea excavata d’Orbigny, D. explanata De Fromentel, Dimorphocoeniopsis alpina (Koby), Ellipsocoenia lorioli (Koby), Enallhelia compressa (Münster), E. rathieri d’Orbigny, Epistreptophyllum cf. densum Roniewicz, Fungiastraea moeschi (Koby), Heliocoenia corallina Koby, H. humberti Étallon, H. minima Sikharulidze, Heterocoenia cf. inflexa (Eichwald), Latiphyllia neocomiensis De Fromentel, Latiastrea mucronata Sikharulidze, Latomeandra sp., Meandrastrea rudis (De Fromentel)(new combination), M. cf. lamberti (Bataller), Meandrophyllia corrugata (Michelin), Microsolena major (Ferry), M. cf. subexcavata Eguchi, Mitrodendron cf. modicum Eliášová, Mixastraea polyseptata Morycowa, Montlivaltia arcuata Beauvais, M. kaufmanni Koby, M. truncata (Defrance, 1817), Myriophyllia cf. propria Sikharulidze, Paraclausastrea vorarlbergensis Baron-Szabo, Peplosmilia stutzi (Koby), Placocoenia heimi (Koby)(new combination), Placophyllia dianthus (Goldfuss), Plesiomontlivaltia paucisepta (Koby)(new combination), Pleurophyllia schmidti (Koby)(new combination), P. tobleri (Koby), Polyphylloseris icaunensis (d’Orbigny, 1850), Rhipidogyra cf. minima Koby, Stylangia cf. laddi Wells, Stylina pleionantha Meneghini, S. decipiens Étallon, S. cf. sparsa Trautschold, Stylosmilia alpina Koby, S. yabei Eguchi, Thecosmilia dichotoma (Koby), Th. sp., Trigerastraea gourdani (De Fromentel), and Vallimeandra cf. explanata (De Fromentel). Furthermore, five additional Berriasian coral faunas are reviewed and compared with the coral fauna of the upper Oehrli Formation. These five assemblages are from southern Ukraine (2 assemblages, consisting of five and 12 species, respectively), northern Tunisia (13 species), southern Spain (23 species), and central Tibet (11 species). Except for the faunas from central Tibet and northern Tunisia, the Berriasian coral assemblages are distinctly dominated by colonial species (70–95%); they represent largely isolated populations of mostly endemic species; and consist largely of genera that had already appeared in the Upper Jurassic (80–100%). On the species-level, however, with the exception of the coral assemblage of Spain, the Beriasian coral faunas are dominated by or completely consist of taxa that have their first occurrence in the Berriasian (54–100%). The Berriasian fauna of the upper Oehrli Formation described in this work contains nearly three times more species than found in the contemporaneous fauna of southern Spain which up to now was the largest known Berriasian fauna. Two of the upper Berriasian taxa described in the current work (Cycloria and Placocoenia) may be the first representatives of lineages that still occur today (Mussidae and Montastraeidae, respectively) as suggested by a recent study of the cox1 Intron in modern corals.